1989
DOI: 10.1111/j.1749-6632.1989.tb14935.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cortical Cataractogenesis: IX Activity of Vitamin E and Esters in Preventing Cataracts and γ‐Crystallin Leakage from Lenses in Diabetic Rats

Abstract: Normal and streptozotocin diabetic female Wistar rats were given vitamin E in the diet as the tocopherol, acetate, or succinate form (2,850 IU/kg food). At the end of 6 weeks, the rats were examined for weight gain or loss, general body condition, and cataracts. At sacrifice, blood was collected for measurement of serum glucose, and gamma-crystallin levels were measured in aqueous and vitreous humors using a radioimmunoassay. One lens was homogenized in 8 M guanidinium chloride for ATP analysis. In normal rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Unfortunately their work did not describe the appearance of the lenses, so for the short term experiments it is not specifically known that the lenses were clear, as is the case at 1 and 2 weeks in the diabetic rat. The loss of ATP was previously shown to occur in all sugar cataracts even though the lens remained clear when treated with antioxidants such as BHT (Linklater et al, 1986), vitamin E (Trevithick et al, 1989), vitamin C (Linklater et al, 1990) and vitamin A (Linklater et al, 1992). A possible explanation of this was noted by , who observed that early in the precataractous stages of model diabetic cataract loss of mitochondria occurred.…”
Section: Short-term Precataractous Stage Of Diabetes (No Taurine Suppmentioning
confidence: 86%
“…Unfortunately their work did not describe the appearance of the lenses, so for the short term experiments it is not specifically known that the lenses were clear, as is the case at 1 and 2 weeks in the diabetic rat. The loss of ATP was previously shown to occur in all sugar cataracts even though the lens remained clear when treated with antioxidants such as BHT (Linklater et al, 1986), vitamin E (Trevithick et al, 1989), vitamin C (Linklater et al, 1990) and vitamin A (Linklater et al, 1992). A possible explanation of this was noted by , who observed that early in the precataractous stages of model diabetic cataract loss of mitochondria occurred.…”
Section: Short-term Precataractous Stage Of Diabetes (No Taurine Suppmentioning
confidence: 86%
“…The importance of oxidative stress in various types of experimentally induced cataractogenesis is well established [10] but its role in diabetes-induced cataractogenesis remains a subject of debate. Some reports indicate an important role for oxidative damage in the onset and progression of diabetic cataracts [11], but others failed to demonstrate any substantial retardation of post-translational modification of lens crystallins [12] or cataract formation [13] with antioxidant therapy. At the same time, numerous studies in models of diabetes and galactosaemia suggest that the loss of major antioxidants such as reduced glutathione (GSH), taurine, and ascorbate is a result of osmotic compensation [14±16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are several nonenzymatic free radical scavengers, such as glutathione [11], ascorbate [12] and vitamin E [13]. Some metabolic events may lead to alterations in the activities of these enzymes leading to an increase in free radical production.…”
Section: Introductionmentioning
confidence: 99%